Ocorrência de moscas ectoparasitas (Diptera, Streblidae e Nycteribiidae) de morcegos (Mammalia, Chiroptera) no cerrado de Brasília, Distrito Federal, Brasil - Graciolli,Gustavo (2002)
Two species of Basilia Miranda Ribeiro, 1903 (Nycteribiidae) and eigth species of Streblidae were collected from Brasília. Basilia anceps Guimarães & D' Andretta, 1956; B. hughscotti Guimarães & D' Andretta, 1956; Megistopoda aranea (Coquillet, 1899); M. proxima (Séguy, 1926) and Neotrichobius delicatus (Machado-Allison, 1966) are collected for the first time at the Federal District.